Hypercoagulopathy as a severe Long-term complication of post SARS-CoV-19 infection - Xinhai R. Zhang; Indu Agarwal; Jian Jing; Lin Cheng; Gladson Scaria; Mamoor Latef; Paolo Gattuso (Elsevier, 2022)
Two years since the advent of the COVID-19 pandemic, it is time to discuss the long-term complications post virus infection. We are reporting three autopsy cases from patients who had COVID-19 one to six months before death. All three patients were SARS-CoV-2 negative at admission but expired shortly. At autopsy, the first patient showed subacute diffuse myocardial ischemic injury with microthrombi in pericardial small vessels, whereas the second patient showed catastrophic acute and subacute pulmonary infarctions with hemothorax leading to respiratory failure. The third patient showed subacute severe cerebral infarcts in the left middle cerebral artery region. Our findings suggest the hypercoagulopathy and subsequent vital organ damage may persist beyond the active phase of SARS-CoV-2 infection. It is essential to continue monitoring the COVID-19 patients after recovery, so as to identify those with vital organ injury in a timely manner and to take necessary steps to prevent severe consequences of COVID-19 complications.